A Method for Supporting Aesthetic Design Based on the Analysis of the Relationships between Customer Kansei and Aesthetic Element. Issue 3 (3rd May 2016) - Kobayashi, Masakazu; Kinumura, Takuma; Higashi, Masatake
ABSTRACT: Due to maturation of science and technology, companies are required to differentiate their products in terms of subjective qualities such as aesthetics whose evaluation heavily depends on customer feeling i.e. kansei. In this research, we develop a new aesthetic design support method based on analysis of customer kansei. In the proposed method, a customer makes kansei evaluations of existing products. Based on their result, a three-layer model that represents the relationships between customer's kansei and product aesthetics is constructed by using SOM (Self-organizing map) and traditional artificial neural network. After constructing the model, a customer indicates his / her needs for a new product and optimal aesthetic design is explored by using genetic algorithm. In the case study, the proposed method is applied to office chair design and its effectiveness is confirmed. GRAPHICAL ABSTRACT: